Competing orders, competing anisotropies, and multicriticality: The case of Co-doped YbRh2 Si2 - Andrade, Eric C. [UNESP]; Brando, Manuel; Geibel, Christoph; Vojta, Matthias (American Physical Society (APS), 2014)
Motivated by the unusual evolution of magnetic phases in stoichiometric and Co-doped YbRh2Si2, we study Heisenberg models with competing ferromagnetic and antiferromagnetic ordering combined with competing anisotropies in exchange interactions and g factors. Utilizing large-scale classical Monte Carlo simulations, we analyze the ingredients required to obtain the characteristic crossing point of uniform susceptibilities observed experimentally near the ferromagnetic ordering of Yb(Rh0.73Co0.27)2Si2. The models possess multicritical points, which we speculate to be relevant for the behavior of clean as well as doped YbRh2Si2. We also make contact with experimental data on YbNi4P2, where a similar susceptibility crossing has been observed. © 2014 American Physical Society.